DeFries-Fulker analysis of longitudinal reading performance data from twin pairs ascertained for reading difficulties and from their nontwin siblings - Astrom, Raven L. (2011)
Reading difficulties are both heritable and stable; however, little is known about the etiology of this stability. Results from a preliminary analysis of data from 56 twin pairs who participated in the Colorado Longitudinal Twin Study of Reading Disability (Astrom et al., 2007) suggested that about two-thirds of the proband deficit at follow-up was due to genetic factors that also influenced deficits at their initial assessment. Although our proband sample is now nearly twice as large, it is still relatively small; thus, to increase power, we subjected data from probands, co-twins and their nontwin siblings to a novel extension of DeFries-Fulker analysis (DeFries & Fulker, 1985; 1988). In addition to providing estimates of univariate and bivariate heritability, this analysis facilitates a test of the difference between shared environmental influences for twins versus siblings. Longitudinal composite reading performance scores at 10.6 and 15.5 years of age, on average, were analyzed from 33 MZ and 64 DZ twin pairs in which at least one member of each pair had reading difficulties, and from 44 siblings of the probands. Scores were highly stable (.86 ± .03, across probands, cotwins and siblings) and heritability of the group deficit at initial assessment was .67 ± .22. Longitudinal bivariate heritability was .59 ± .21, suggesting that nearly 60% of the proband reading deficit at follow-up is due to genetic factors that influenced reading difficulties at the initial assessment. However, tests for special twin environmental influences were nonsignificant.